Computer Simulation and Modeling in Pharmacokinetics and Pharmacodynamics - Chawla R.; Rani V.; Kumar K.; Mishra M. (My University, 2025)
Computer-based modeling and simulation is emerging as a useful tool to complement the analysis and interpretation of biological data. The large volume, scale, and complexity of data generated from in vitro, in vivo, and ex vivo data cannot be analyzed and interpreted by conventional data analysis tools. So, various in silico computational e-resources, databases, and simulation softwares are being used for the determination of pharmacokinetic (PK) and pharmacodynamic (PD) parameters for the management of diseases. These tools help in providing multiscale representation of the biological processes in the order of increasing complexity from that of protein and genes, cells, isolated tissues and organs, and the whole organism. The United States Food and Drug Administration (USFDA) has also directed the use of PK/PD simulation for the evaluation of drugs during the clinical phase, in which the primary focus is on the establishment of relationship between therapeutic drug concentration and patient response. The aim of this chapter is to discuss the role, advancement, and development of biocomputational tools used in research and development in the pharmaceutical industry, wherein the number of experimental studies is exponentially growing. Furthermore, application of these studies to optimize the dosing regimens, dose-response relationship, etc. will be discussed. © Springer Nature Singapore Pte Ltd. 2022.